Questioning Chinese government's stand for sovereign immunity. Issue 1 (2nd January 2017) - Rahman, Ferdous
Abstract: Since last decade, restrictive sovereign immunity has been growing as an international comity among the states. Because of the absence of effective international conventions in this regards, states are following their own statutory law on this matter. However, China has always advocated for absolute sovereign immunity principles for itself as well as other states before its courts. The underlying reasons behind such approach in China were – its Socialist ideology considering restrictive sovereign immunity principle as bourgeoistic and colonialist; Confucius teaching of non-amenable nature of sovereign power; deep-rooted fear to accept foreign court's jurisdiction due to its history of unequal and disgraceful treaties with foreign states. Also, the statement of China's diplomatic notes is not in consistence with its practice. There are several cases where it did not claim sovereign immunity for its agents or instrumentalities. Therefore, in the present context, it can be suggested that China makes its stand for sovereign immunity clear in terms of both diplomatic statements and practice. It is advisable for China to adopt restrictive sovereign immunity in order to make its legal stand coherent with international practices.